Polymerase Chain Reaction Detection of Trypanosoma cruzi in Macaca fascicularis Using Archived Tissues - Williams, Jeff T.; Mubiru, James N.; Schlabritz-Loutsevitch, Natalia E.; Rubicz, Rohina C.; VandeBerg, John L.; Dick Jr, Edward J.; Hubbard, Gene B. (The American journal of tropical medicine and hygiene, 2009)
This study describes conventional and real-time polymerase chain reaction (PCR) methods developed to detect and quantify Trypanosoma cruzi DNA in cynomolgus monkeys (Macaca fascicularis) using formalin-fixed paraffin-embedded blocks archived for periods of up to 6 years. The highest concentration of T. cruzi DNA was found in the myocardium, urinary bladder, stomach, lymph node, adrenal gland, and colon. The concentration of T. cruzi DNA detected in cardiac tissues was 10–100- fold greater than found elsewhere; the mean concentrations of T. cruzi DNA in non-cardiac tissues were otherwise comparable. Trypanosoma cruzi DNA was amplified from cerebrum but not cerebellum or kidney. Successful use of DNA from formalin-fixed, paraffin-embedded blocks is important because most pathology laboratories routinely archive wax blocks. This archived resource can be used for further studies on the prevalence of this disease.
Keywords: Polymerase Chain Reaction; Trypanosoma cruzi; Macaca fascicularis; Archived Tissues